2018
DOI: 10.1177/0956797618813538
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Has Better Fidelity Than Long-Term Memory: The Fidelity Constraint Is Not a General Property of Memory After All

Abstract: How detailed are long-term-memory representations compared with working memory representations? Recent research has found an equal fidelity bound for both memory systems, suggesting a novel general constraint on memory. Here, we assessed the replicability of this discovery. Participants (total N = 72) were presented with colored real-life objects and were asked to recall the colors using a continuous color wheel. Deviations from study colors were modeled to generate two estimates of color memory: the variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 44 publications
4
35
1
Order By: Relevance
“…Future work may also extend our approach to look at other stimulus dimensions, such as color (Biderman et al, 2019;Brady et al, 2013), orientation (Korkki et al, 2020), shape (A. Y. Li, Liang, Lee, & Barense, 2020), and faces (Lorenc, Pratte, Angeloni, & Tong, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future work may also extend our approach to look at other stimulus dimensions, such as color (Biderman et al, 2019;Brady et al, 2013), orientation (Korkki et al, 2020), shape (A. Y. Li, Liang, Lee, & Barense, 2020), and faces (Lorenc, Pratte, Angeloni, & Tong, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tasks like the one used in the present work can allow us to distinguish failure of retrieval from imprecise retrieval of the target location. In particular we can use a mixture modeling approach to do so (see, e.g., Biderman, Luria, Teodorescu, Hajaj, & Goshen-Gottstein, 2019;Brady, Konkle, Gill, Oliva, & Alvarez, 2013;Richter, Cooper, Bays, & Simons, 2016;W. Zhang & Luck, 2008).…”
Section: Distinguishing the Success And (Im)precision Of Recallmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent conceptual replication of the Brady et al (2013) study, using a larger number of participants and a Bayesian analysis, found evidence for a larger von Mises standard deviation in recall from long-term memory than on a three-item working memory task ( Biderman, Luria, Teodorescu, Hajaj, & Goshen-Gottstein, 2018 ). Like the Rademaker et al study, this finding is consistent with the predictions of our model.…”
Section: Resultsmentioning
confidence: 98%
“…In this study, we examine whether sustained and spatial attention exert distinct or common influences on long-term memory encoding using behavioral and neural signatures. To measure long-term memory behavior with high sensitivity, we employed a continuous report task, in which participants report a particular dimension of a stimulus along a continuous space (Biderman et al, 2019;J. E. Fan & Turk-Browne, 2016;Richter et al, 2016;Sutterer & Awh, 2016;Tompary et al, 2020;Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%